PERKEMBANGAN MANAJEMEN PERUBAHAN PADA UMKM KRIPIK BALADO SALSABILA PARAK KARAKAH - Nike Puspita Sari; Miftahul Hamdi; Widya Veronika Puti; Wulan Oktavia; Ramdani Bayu Putra (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Abstrak. This research aims to find out how change management has developed in the UMKM Kripik Balado Salsabila Parak Karakah. The object of this research is the UMKM Balado Chips Salsabila Parak Karakah. The data collection methods used were interviews and documentation. Based on the results obtained from the Balado Salsabila Chips that have been carried out above, it was found that overall the Balado Salsabila Chip SMEs have experienced significant changes from year to year. The changes are in terms of product marketing which has shifted from offering it to shops to using the internet and social media. Chip Balado Salsabila makes changes and developments every year to streamline the production and marketing process as well as product sales and also contribute to PRDB in Padang City to improve community welfare.